2
$\begingroup$

I have to take the nth derivative of a function (below). The research paper, which I have taken it from calls it the composite function. Any idea how to find the solution?

$$L_d(s) = exp\{-C_d s^{2/\alpha_N}\}$$

I can take as many derivates as I want manually, but cannot find the $nth$ derivate or any formula for it, For example see below:

$$F' = -\dfrac{2C_dx^{\frac{2}{\alpha_N}-1}\mathrm{e}^{-C_dx^\frac{2}{\alpha_N}}}{\alpha_N}$$

$$F'' = \dfrac{2C_dx^{\frac{2}{\alpha_N}-2}\left(2C_dx^\frac{2}{\alpha_N}+\alpha_N-2\right)\mathrm{e}^{-ax^\frac{2}{\alpha_N}}}{\alpha_N^2}$$

Any guidance would be appreciated for $F^n$

$\endgroup$
2
$\begingroup$

A formula to calculate the $n$-th derivative of composite functions is stated as identity (3.56) in H.W. Gould's Tables of Combinatorial Identities, Vol. I and called:

Hoppe Form of Generalized Chain Rule

Let $D_s$ represent differentiation with respect to $s$ and $z=z(s)$. Hence $D^n_s g(z)$ is the $n$-th derivative of $g$ with respect to $s$. The following holds true \begin{align*} D_s^n g(z)=\sum_{k=0}^nD_z^kg(z)\frac{(-1)^k}{k!}\sum_{j=0}^k(-1)^j\binom{k}{j}z^{k-j}D_s^nz^j \end{align*} In the special case \begin{align*} g(z(s))=e^{z(s)} \end{align*} we have $$D_z^kg(z)=D_z^k e^z=e^z$$ and obtain \begin{align*} D_s^ne^z=e^z\sum_{k=0}^n\frac{(-1)^k}{k!}\sum_{j=0}^k(-1)^j\binom{k}{j}z^{k-j}D_s^nz^s\tag{1} \end{align*}

We consider \begin{align*} z=z(s)=as^b\tag{2} \end{align*} which corresponds to $L_d(s) = exp\{-C_d s^{2/\alpha_N}\}$ with $a=-C_d$ and $b=\frac{2}{\alpha_N}$.

From (1) and (2) we obtain for $n>0$: \begin{align*} \color{blue}{D_s^n\exp\left(as^b\right)} &=\exp\left(as^b\right)\sum_{k=0}^n\frac{(-1)^k}{k!}\sum_{j=0}^k(-1)^j\binom{k}{j}\left(as^b\right)^{k-j}D_s^n\left[\left(as^{b}\right)^j\right]\\ &=\exp\left(as^b\right)\sum_{k=0}^n\frac{(-1)^k}{k!}\sum_{j=0}^k(-1)^j\binom{k}{j}a^{k-j}s^{b(k-j)}D_s^n\left(a^js^{bj}\right)\\ &=\exp\left(as^b\right)\sum_{k=0}^n\frac{(-1)^k}{k!}a^k\sum_{j=0}^k(-1)^j\binom{k}{j}s^{b(k-j)}D_s^n\left(s^{bj}\right)\\ &\color{blue}{=\exp\left(as^b\right)\sum_{k=1}^n\frac{(-a)^k}{k!}\left(\sum_{j=1}^k(-1)^j\binom{k}{j}{(bj)}^{\underline{n}}\right)s^{bk-n}}\tag{3}\\ \end{align*} with $m^{\underline{n}}=m(m-1)\cdots(m-n+1)$ the falling factorial.

In the last line the inner sum contains a factor $j$ if $n>0$. We can therefore start with the lower bound $j=1$ and so also with $k=1$.

Example: $n=1$:

We obtain from (3) \begin{align*} \exp&\left(as^b\right)\sum_{k=1}^1\frac{(-a)^k}{k!}\left(\sum_{j=1}^k(-1)^j\binom{k}{j}bj\right)s^{bk-1}\\ &=\exp\left(as^b\right)\left(\frac{(-a)^1}{1}\left[(-1)\binom{1}{1}b\right]\right)s^{b-1}\\ &=\exp\left(as^b\right)abs^{b-1}\tag{4} \end{align*}

Substituting $a=-C_d,b=\frac{2}{\alpha_N}$ in (4) gives \begin{align*} \color{blue}{\exp\left(-\frac{2C_d}{\alpha_N}\right)\left(-\frac{2C_d}{\alpha_N}\right)s^{\frac{2}{\alpha_N}-1}} \end{align*} in accordance with OPs calculation.

Example: $n=2$:

We obtain from (3)

\begin{align*} \exp&\left(as^b\right)\sum_{k=1}^2\frac{(-a)^k}{k!}\left(\sum_{j=1}^k(-1)^j\binom{k}{j}bj(bj-1)\right)s^{bk-2}\\ &=\exp\left(as^b\right)\left(\frac{(-a)^1}{1}\left[(-1)\binom{1}{1}b(b-1)\right]\right.s^{b-2}\\ &\qquad\qquad\qquad\left.+\frac{(-a)^2}{2!}\left[(-1)\binom{2}{1}b(b-1)+\binom{2}{2}2b(2b-1)\right]s^{2b-2}\right)\\ &=\cdots\\ &=\exp\left(as^b\right)\left(ab(b-1)s^{b-2}+a^2b^2s^{2b-2}\right)\tag{5} \end{align*}

Substituting $a=-C_d,b=\frac{2}{\alpha_N}$ in (5) gives \begin{align*} \exp&\left(-\frac{2C_d}{\alpha_N}\right)\left(\left(-C_d\right)\frac{2}{\alpha_N}\left(\frac{2}{\alpha_N-1}\right)s^{\frac{2}{\alpha_N-2}}+C_d^2\frac{4}{\alpha_N^2}s^{\frac{4}{\alpha_N-2}}\right)\\ &=\color{blue}{\exp\left(as^b\right)\frac{2C_d}{\alpha_N^2}\left(\alpha_N-2+2C_ds^{\frac{2}{\alpha_N}}\right)} \end{align*} in accordance with OPs calculation.

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Thanks for your response. To simplify, the solution that I have shared, is it correct as yours one is a bit complex on the face of it... But I appreciate the reply. $\endgroup$ – Kashan Jan 24 '18 at 0:24
  • $\begingroup$ @Sjaffry: You're welcome. After work I'll add some comments and an example which might help to clarify things. $\endgroup$ – Markus Scheuer Jan 24 '18 at 7:52
  • 1
    $\begingroup$ @Sjaffry: I've added examples which show your calculations are correct. Good work. :-) Hint: It's preferable to stick at the same notation. In your case the function $L_d$ and the variable $s$. Otherwise you should explicitly mention the notational change. $\endgroup$ – Markus Scheuer Jan 24 '18 at 15:00
  • $\begingroup$ Thanks for the detailed answer. The only reason I accepted my answer as the solution is that it simplifies the approach, though your approach gives the exact formula for the same thing. I appreciate your time and learned from your response. $\endgroup$ – Kashan Jan 25 '18 at 21:28
  • 1
    $\begingroup$ @Sjaffry: You're welcome! $\endgroup$ – Markus Scheuer Jan 25 '18 at 21:38
0
$\begingroup$

Can we do the following (is it correct?)

Since we have the formula: $f(x) = e^x = \sum^{\infty}_{j=0} \frac{x^j}{j!}$

Hence, $$f(x) = e^{Ax^{2/b}} = \sum^{\infty}_{j=0} \frac{(Ax^{2/b})^j}{j!}$$ $$f(x) = \sum^{\infty}_{j=0} \frac{A^j}{j!}(x^{2j/b})$$

Then, let $z = x^{p\ j}$, where $p = 2/b$

$$ Z^1 = \frac{d}{dx}(x^{p \ j}) = (pj)x^{p\ j-1}$$ $$ Z^2 = \frac{d}{dx}(Z^1) = (pj)(p j-1)x^{p\ j-2}$$ $$ Z^3 = (pj)(p j-1)(p j-2)x^{p\ j-3}$$ $$ Z^3 = (pj)(p j-1)(p j-2)(p j-3)x^{p\ j-4}$$

Then

$$ Z^n = (pj)(pj-1)(pj-2)...(pj-n+1)x^{p\ j-n}$$

So, $F^n = \frac{f^n}{f^nx}$ is:

$$ F^n = \sum^{\infty}_{j=0} \frac{A^j}{j!} (pj)(pj-1)(pj-2)...(pj-n+1)x^{p\ j-n}$$

$$ F^n = \sum^{\infty}_{j=0} \frac{A^j}{j!} x^{p\ j-n} (pj)_n$$

Where $(.)_n$ is the falling factorial

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.